2008
DOI: 10.1038/nri2395
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells in health and disease

Abstract: Mesenchymal stem cells (MSCs) are a heterogeneous subset of stromal stem cells that can be isolated from many adult tissues. They can differentiate into cells of the mesodermal lineage, such as adipocytes, osteocytes and chondrocytes, as well as cells of other embryonic lineages. MSCs can interact with cells of both the innate and adaptive immune systems, leading to the modulation of several effector functions. After in vivo administration, MSCs induce peripheral tolerance and migrate to injured tissues, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

33
2,712
2
51

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 3,179 publications
(2,798 citation statements)
references
References 118 publications
33
2,712
2
51
Order By: Relevance
“…The systemic injection of MSCs and NPCs is remarkably immune regulatory in vivo (Martino and Pluchino, 2006;Spaggiari and Moretta, 2012;Uccelli et al, 2008).…”
Section: Modulation Of Immune Responsesmentioning
confidence: 99%
“…The systemic injection of MSCs and NPCs is remarkably immune regulatory in vivo (Martino and Pluchino, 2006;Spaggiari and Moretta, 2012;Uccelli et al, 2008).…”
Section: Modulation Of Immune Responsesmentioning
confidence: 99%
“…However, it has recently been shown, that embryonic MSC derived from the neuroepithelium and neural crest (68). It has been suggested that in post-natal life the relative importance of MSC derived from other developmental lineages decreases due to the increasing importance of mesodermal MSC (69). Because of the differentiation capacity, it has been proposed that MSC could be used for the regeneration of different tissues.…”
Section: Ig Gene Rearrangementmentioning
confidence: 99%
“…1 Adipogenesis and osteogenesis have a reciprocal relationship in common mesenchymal precursor cells. 2 Disruption of the balance in these processes during MSC differentiation leads to disorders, such as obesity, skeletal fragility, and osteoporosis.…”
mentioning
confidence: 99%
“…2 Disruption of the balance in these processes during MSC differentiation leads to disorders, such as obesity, skeletal fragility, and osteoporosis. 1 MSC differentiation is regulated by specific transcription factors. MSCs differentiate into adipocytes when they express peroxisome proliferator-activated receptor g 2 (PPARg 2 ), which enhances expression of adipogenic genes.…”
mentioning
confidence: 99%